A metrological device for robot identification. (February 2022) - Garnier, Sebastien; Subrin, Kevin
Abstract: Nowadays, industrial robots are increasingly used for heavy manufacturing tasks such as milling, drilling, deburring or sanding. Twenty years ago, researchers began to identify scientific bottlenecks and have made contributions on robot performance in terms of repeatability and accuracy. We are currently observing many methods and tools to apply to improve robot performances through their geometric, kinematic and dynamic modeling. There are often laboratory tools, not compatible with the needs of companies i.e. economically compatible, easy to install, easy to use with a good integration to industrial lines. In this context, we propose a new device to identify robot performances based on the famous ballbar used for the calibration of machine-tools. This paper thus deals with the design methodology, its design and environment of use as well as its performance in robot identification. Graphical abstract: Highlights: Methodology for designing a metrological device for robot performance improvement. Metrological device for both loading an industrial robot (up to 2500N) and measuring its deformation. Finite Element Analysis to understand the system behavior under stress. Validation test of the repeatability of the device.